The prevalence of cardiovascular risk factors among the followers of the Seventh-day Adventist Church living in the South of Poland - Majda, Anna; Zalewska-Puchał, Joanna; Bodys-Cupak, Iwona; Kamińska, Alicja; Suder, Marcin (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. For half a century cardiovascular diseases remain unchanged as the most important cause of mortality of Polish residents. There is little amount of tests determiningthe risk factors for these diseases among religious groups, although interest in this topic among public health practitioners is increasing. Aim. The aim of this study was to determine some factors of cardiovascular risk and the risk of cardiovascular events among Seventh-day Adventists (SDA). Material and methods. The study has been conducted among 118 randomly selected SDA Church members and based on the results of: anthropometric measurements, physical examination, laboratory tests (C-reactive protein [CRP], homocysteine, glucose, total cholesterol, HDL and triglycerides) and assessing the risk ofcardiovascular events based on the SCORE scale. Statistical analysis was based on the chi-square test and ANOVA. Founded significance level was 0.05. Results. More than a half of the respondents were diagnosed elevated homocysteine level and gluteal-femoral obesity. Less than half of those surveyed had elevated total cholesterol levels and increased blood pressure, almost one-quarter of the respondents had raised triglyceride levels, at one-tenth had heightened glucose and CRP levels. An important variable modifying the risk of cardiovascular diseases proved to be gender of the respondents. Conclusions. The risk assessment of diseases of the cardiovascular system SDA Church representatives revealed that among the modifiable factors-biochemical levels of homocysteine proved to be the most important new risk factor, but among the classic factors-blood pressure value. There was a small and moderate risk of cardiovascular events in the study group. Nursing Topics 2015; 23 (2): 190–196